KEDUDUKAN SBKRI (SURAT BUKTI KEWARGANEGARAAN REPUBLIK INDONESIA) TERHADAP HAK WNI KETURUNAN TIONGHOA DITINJAU DARI HUKUM HAM INTERNASIONAL - Pratiwi, Anggun; Suksma Prijandhini Devi Salain, Ni Made (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 04, Juni 2013)
SBKRI or “Surat Bukti Kewarganegaraan Indonesia” is a document stating that theowner is a citizen of the Republic of Indonesia, especially for Indonesian citizens ofChinese descent. It is regulated under the Law of the Republic of Indonesia year 1985about Citizenship in Republic of Indonesia. However, SBKRI is now often used as anexcuse by some unscrupulous government officials to obstruct the rights of anIndonesian citizen of Chinese descent in particular on the management of thebureaucracy such as birth registration to apply passport. This paper will describe theSBKRI’s position against the rights of Indonesian citizens of Chinese descent in thefullfilment of rights and obligations as an Indonesian citizen of Chinese descent. Thispaper will also discuss how the protection of human rights associated with the presenceof SBKRI.
Keywords: citizen, Chinese, human rights